FISCAL DECENTRALIZATION AND INVESTMENT TOWARDS ECONOMIC GROWTH IN ISLAMIC PERSPECTIVE - Rosviana, Mohammad Irfan (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2025)
This study aims to determine the effect of the General Allocation Fund (DAU), Special Allocation Fund (DAK) and Investment on Gross Regional Domestic Income (GRDP) in an Islamic economic perspective. The research approach carried out in this study is quantitative with secondary data. The data collection technique in this study used purposive sampling with data sourced from the Central Statistics Agency, Ministry of Finance and Bappenas. The data processing tool in this study used SPSS25 software. The result of this study is that the General Allocation Fund variable affects the Gross Regional Domestic Product, the result of the Special Allocation Fund variable does not affect the Gross Regional Domestic Product and the investment variable affects the Gross Regional Domestic Product. In the perspective of Islamic economics, economic growth is not only to grow and advance the material and spiritual side of human beings. The measurement of economic growth in the Islamic economy is the same as conventional, but there are additional aspects of zakat, infaq and alms in the calculation of GNP, GDP and GDP. In the discussion of Islamic economics can be used as a measure to see economic growth and community welfare through people's per capita income income which is a parameter of falah in it.